The southernmost records of Brotula barbata (Bloch & Schneider 1801) (Ophidiiformes: Ophidiidae) in the western Atlantic Ocean. Issue 4 (23rd October 2018) - Bauer, Arthur B.; Fischer, Luciano G.; Tomás, Acácio R. G.; Santos, Roberta A.; Mincarone, Michael M.
Abstract : The present study reports the occurrence of the bearded brotula, Brotula barbata, in four different localities off southern Brazil. These records extend the species' known distribution limit southwards, beyond Rio de Janeiro, to the state of Rio Grande do Sul (30° 50′ S). Morphometric and meristic data for the specimens reported herein are provided and discussed.